Efficient three-dimensional modelling of high-rise building structures - Jameel, Mohammed; Islam, A. B. M. Saiful; Khaleel, Mohammed; Amirahmad, Aslam (Journal of Civil Engineering and Management, 2013)
A multi-storey building is habitually modelled as a frame structure which neglects the shear wall/slab openings along with the inclusion of staircases. Furthermore, the structural strength provided by shear walls and slabs is not precisely incorporated. With increasing building height, the effect of lateral loads on a high-rise structure increases substantially. Inclusion of shear walls and slabs with the frame leads to improved lateral stiffness. Besides, their openings may play imperative role in the structural behaviour of such buildings. In this study, 61 multi-storey building configurations have been modelled. Corresponding analyses are performed to cope with the influence of shear walls, slabs, wall openings, masonry walls and staircases in addition to frame modelling. The finite element approach is used in modelling and analysis. Structural responses in each elemental combination are evaluated through equivalent static and free vibration analyses. The assessment reveals that inclusion of only slab components with frame modelling contributes trivial improvement on structural performance. Conversely, the presence of shear wall slabs with frame improves the performance noticeably. Increasing wall openings decreases the structural responses. Furthermore, it is not recommended to model staircases in addition to frame–slab–shear wall modelling, unless the effect of wall openings and slab openings is adequately considered.First published online: 24 Oct 2013